Phytochemistry of some Useful forest Plants - Dayal, Rameshwar (Indian Forester, 2004)
Phytochemistry is the study of extraction, isolation and identification of plant chemicals viz; alkaloids, iridoides, phenolics, steroids, coumarins, terpenoides and others. These secondary metabolites play key role in the development of many new sources of plant - derived products. The isolation and characterization of new bioactive constituents from plants have become possible with the advent of latest sophisticated techniques such as chromatographic methods, multidimensional NMR and mass spectrometry. About one hundred twenty compounds were characterized using GC-MS for essential oils and latest spectroscopic methods like 2D NMR and other techniques for the pure compounds of which four compounds namely; artoflavanone, stipulin, luteolin-4'- rutinoside and quercetin-3-0-digalactoside were found to be new. A number of compounds were found to possess medicinal activity. This paper describes the isolation and characterization of chemical constituents from the different parts of nine plant species having biological activity.